2008
DOI: 10.1021/jp801229g
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study on Water and Oxygen Adsorption on Surfaces of Indium Oxide and Indium Tin Oxide Nanoparticles

Abstract: We present a first-principles study on surface structures of In2O3 and indium tin oxide (ITO) nanoparticles upon exposure to O2 and H2O molecules. It was found that dissociative chemisorption of O2 and H2O is facile on the metal-terminated oxide surfaces. O2 chemisorption is energetically more favorable than H2O dissociative chemisorption until the metal-terminated surfaces are saturated by chemisorbed O2 dimers, at which point the surfaces become virtually identical to the O-terminated surfaces and the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
5
41
0
Order By: Relevance
“…A dimerized surface would be in agreement with other DFT calculations, which predict that surface oxygen atoms undergo a dimerization. 3,24 For the sputtered/annealed surface, we can safely rule out a (partial) peroxide termination for the following reasons: (i) The preparation included annealing to 800 K in an oxygen background pressure of less than 10 −12 mbar. This corresponds to an oxygen chemical potential of approximately −2 eV, assuming equilibrium with the residual gas.…”
Section: A Surface Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A dimerized surface would be in agreement with other DFT calculations, which predict that surface oxygen atoms undergo a dimerization. 3,24 For the sputtered/annealed surface, we can safely rule out a (partial) peroxide termination for the following reasons: (i) The preparation included annealing to 800 K in an oxygen background pressure of less than 10 −12 mbar. This corresponds to an oxygen chemical potential of approximately −2 eV, assuming equilibrium with the residual gas.…”
Section: A Surface Structurementioning
confidence: 99%
“…1,18,24,[36][37][38] The CB is dominated by the In 5s states. Gap states of pure In 2 O 3 have been reported previously.…”
Section: Surface Statesmentioning
confidence: 99%
“…11,21 Meanwhile, the adsorption of oxygen on ITO surface is commonly observed during oxygen plasma or ultraviolet (UV)-ozone treatments, 22,23 and molecular oxygen and water in the ambient air are also suggested to generate adsorbed oxygen on ITO. 24 Significantly, these adsorbed oxygen species can not only increase the work function of ITO 23,25 but also create midgap charge trap states on the organic semiconductor deposited on top by removing electrons from the organic layer (i.e., oxidation), even resulting in an irreversible degradation of the organic semiconductor as Lo et al reported recently. 23 Under these circumstances, we anticipate a presence of adsorbed oxygen on ITO during the ambient air processing and oxidation of the PFN coming into contact, ultimately inducing the formation of midgap charge trap states in the PFN interfaced with ITO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 Density functional theory studies on the electronic structure of Sn-doped In 2 O 3 have revealed a n-type electrical behavior. [9][10][11][12] The conduction band minimum (CBM) of indium oxide is mainly contributed by the highly delocalized In-5s band. The Sn-5s states are strongly hybridized with the neighboring O-2p states, which donate electrons to the conduction band minimum.…”
mentioning
confidence: 99%